2011
DOI: 10.1016/j.yexcr.2011.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Alexander disease causing mutations in the C-terminal domain of GFAP are deleterious both to assembly and network formation with the potential to both activate caspase 3 and decrease cell viability

Abstract: Alexander disease is a primary genetic disorder of astrocyte caused by dominant mutations in the astrocyte-specific intermediate filament glial fibrillary acidic protein (GFAP). While most of the disease-causing mutations described to date have been found in the conserved α-helical rod domain, some mutations are found in the C-terminal non-α-helical tail domain. Here, we compare five different mutations (N386I, S393I, S398F, S398Y and D417M14X) located in the C-terminal domain of GFAP on filament assembly prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 68 publications
(89 reference statements)
3
30
0
1
Order By: Relevance
“…WB with antibody 1 detected both WT GFAP and GFAP p.(E312*) with the respective expected molecular weight, yet the band intensity of GFAP p.(E312*) was lower than that of WT GFAP (Figure 1h, upper panel). As expected, antibodies 2 and 3 did not detect GFAP p.(E312*) as these antibodies recognize the C-terminal fragment of GFAP 24 that is absent in GFAP p.(E312*) (Figure 1h, middle and lower panels). Taken together, these findings demonstrate that the p.(E312*) mutation truncates the GFAP and lowers expression levels of GFAP.…”
Section: Clinical Findingssupporting
confidence: 71%
See 2 more Smart Citations
“…WB with antibody 1 detected both WT GFAP and GFAP p.(E312*) with the respective expected molecular weight, yet the band intensity of GFAP p.(E312*) was lower than that of WT GFAP (Figure 1h, upper panel). As expected, antibodies 2 and 3 did not detect GFAP p.(E312*) as these antibodies recognize the C-terminal fragment of GFAP 24 that is absent in GFAP p.(E312*) (Figure 1h, middle and lower panels). Taken together, these findings demonstrate that the p.(E312*) mutation truncates the GFAP and lowers expression levels of GFAP.…”
Section: Clinical Findingssupporting
confidence: 71%
“…This cell line was derived from the human adrenal cortex carcinoma, features a vimentin filament network, expresses no endogenous GFAP and is well-suited for assessing mutant GFAP properties. 17,24 Transfection efficiency of SW13 (Vim þ ) cells was B26% in our hands (data not shown). Expressed WT GFAP assembled in 80% of the transfected cells into filamentous networks that partially coaligned with the vimentin IF networks (Figure 3a and d) that is consistent with previous observations.…”
Section: Clinical Findingsmentioning
confidence: 60%
See 1 more Smart Citation
“…We also do not distinguish between the GFAP-␣ and GFAP-␦ isoforms, although ␣ likely represents more than ϳ90% of the total in the CNS (42,43). Differences in solubility exist between the GFAP isoforms and between mutant and wild-type protein (39,41,44,45), although not under the conditions used for extraction in the experiments reported here.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, similar processing steps involving combinations of brain proteases and brain proteins appear to occur in a series of other proteins related to neuronal pathologies, such as trans-activation response (TAR) DNA-binding protein 43, α-synuclein, and more [106108] (Table 3) [109119]. A recent finding indicated that a fragment of tau was present in serum samples, and that it correlated with cognitive function in a small clinical study, highlighting the potential of this approach [120].…”
Section: A Critical Evaluation Of Ongoing Biomarker Approachesmentioning
confidence: 99%